A multi-fiber approach with directional stiffness matrix in reinforced concrete structures. Issue 7 (19th March 2020) - Yousefi, Behrooz; Esfahani, Mohammad Reza; Tavakkolizadeh, Mohammadreza
Abstract : Purpose: This paper aims to develop a new multi-fiber element for predicting the structural behavior of planar-reinforced concrete (RC) members. Design/methodology/approach: In this work, an exact multi-directional stiffness matrix is analytically derived based on the post-cracking bond-slip interaction between concrete and steel bars. The approach is also extended for large displacement analysis using Green–Lagrange finite strain tensor. In the proposed formulation, the weak form of governed differential equations is approximated by a trial-function expansion based on a finite strain-description and an additional degree of freedom for steel bars. Findings: The findings provide a realistic description of cracking in the concrete structure. Numerical studies are conducted to examine the accuracy of the suggested approach and its capability to predict fairly complex responses of RC models. The findings prove that the proposed element can evaluate local and global responses of RC members, and it can be used as a reliable tool to reflect bond-slip effects in large displacement level. This leads to a robust and precise model for non-linear analysis of RC structures. Originality/value: The methodology is capable of simulating coupled inelastic shear-flexural behavior of RC members through local stress field theory and Timoshenko beam model.